The Effect of Plyometric Jump To Box Training on The Jump Height - Munawaroh, Octa; Iyakrus, Iyakrus; Destriani, Destriani (Universitas Negeri Padang, 2024)
This study aimed to assess the impact of plyometric jump to box training on vertical jump height in female basketball athletes from Smandala Mutiara. The research method employed a quasi-experimental design with a one-group pretest-posttest design. The research sample consisted of 30 female basketball athletes from Smandala Mutiara with an average age of 16-18 years. Data analysis was conducted using a t-test with a significance level of 5% (0.05). The intervention in this study involved plyometric jump to box training for 6 weeks, conducted three times a week, aimed at improving vertical jump height. Vertical jump height plays a crucial role in every aspect of basketball, both in defense and offense, and enhances players' technical abilities in various on-court situations. Pretest and posttest data were normally distributed as indicated by the Shapiro-Wilk test (pretest: 0.2, posttest: 0.117). The pretest results for vertical jump test yielded a maximum score of 41, a minimum score of 27, and a mean of 35.47, while the posttest data showed a maximum score of 42, a minimum score of 28, and a mean of 36.30, with an average increase of 0.83. This indicates an improvement in vertical jump height before and after the intervention. The t-test result yielded a calculated t-value of 5.000 > t-table value of 2.045, with p-value of 0.000 < 0.05. The percentage increase in average height was 2.3%. The t-test results indicate that plyometric jump to box training significantly influences the improvement of vertical jump height in female basketball athletes from Smandala Mutiara. Thus, the alternative hypothesis (Ha) is accepted, and the null hypothesis (H0) is rejected. The implication of this research is that plyometric jump to box training affects vertical jump height in female basketball athletes, but the sample size and types of training should be enhanced to further improve athletes' performance.